Comparison of open and robotic nephron sparing surgery: a single centre experience. (January 2017) - Jelley, Clare R; Kurukulaarachchi, Kurukula ASH; Forster, Luke; Bardgett, Harry; Singh, Rajindra; Addla, Sanjai K
Objective: To compare robotic partial nephrectomy (RAPN) with open partial nephrectomy (OPN) to assess efficacy and impact of learning curve. Methods: From 2010 to 2015 159 patients had a partial nephrectomy (82 OPN and 77 RAPN). All data were collected prospectively. We compared the demographics, peri and postoperative outcomes. Results: Mean age was 60 years in both groups; 59% of patients were men. Tumour size was larger in the open group (34 mm vs 30 mm; P <0.08), but RENAL nephrometry scores greater than 6 were comparable (over 60%). Mean ischaemic time was longer in the RAPN group (18 vs 13 minutes; P <0.04) but complication rates were similar. The RAPN cohort had a reduced estimated blood loss (100 ml vs 300 ml; P <0.01) and shorter median hospital stay (2 vs 5 days; P <0.01). Only two patients in each group were margin positive. The RAPN cohort demonstrated reduced estimated blood loss and a trend towards more complex tumours with increasing learning curve. Conclusion: RAPN is superior to OPN in terms of reduced hospital stay and estimated blood loss without compromising oncological outcomes. This service can be delivered safely and effectively in a low to medium volume cancer centre; these results are similar to published figures from high volume international centres.